PENGARUH PEMASANGAN BULU MATA PALSU DAN SCOTCH TAPE TERHADAP KOREKSI BENTUK MATA SIPIT DALAM RIAS WAJAH MALAM - Peni, Yusia; Katin, Yusmar Emmy; Hayatunnufus, Hayatunnufus (Journal of Home Economics and Tourism, 2012)
This study aimed to analyze the effect of fitiing false eyelashes and scotch tape to form narrow eyes correction in the makeup night. Assessment based indicators suggest that the size of the eye visible, crease line in the eyelid, and eyelashes impression that emerged sticking to the ideal shape of the eye. This study includes the type of research experiments. Objects in this study was slanted eyes, while the samples in this study were three women aged 17-21 years old who have eye characterized by narrow eyes. Primary data was collected directly from the panelists to fill out the assessment. The data were analyzed using analysis of variants (ANOVA). Based on data analysis, proving that there is a significant influence of the impression of the size of the eye that looks at F count (47 472)> F table (3.18) test followed by Duncan test with the results of each group showed a significant difference. In kerungan / crease in the eyelid there are influence by F count (78 763)> F table (3.18). Impression of eyelashes that appears obtained value of F count (124 072)> F count (3.18) by Duncan test results showed each group were significantly different.Keywords: false eyelash, narrow eyes correction